Diplomado de Recipientes a Presión: Módulo IV (Dispositivos de Alivio a Presión Conforme a la Sección VIII, Div. 1 del Código ASME) - Rivera Mendoza, Orlando R. (My University, 2007)
UG-125 All pressure vessels within the Scope of this Division, irrespective of size of pressure, shall be provided whit pressure relief devices in accordance with the requirements of UG-125 trough UG-137. It is the responsibility of the user to ensure that the required pressure relief devices are property installed prior to initial operation. These pressure relief devices need not be supplied by the vessel Manufacturer. Unless otherwise defined in this Division, the definitions relating to pressure relief devices in Section 2 of ASME PTC 25 shall apply.
Keywords: Recipientes a presión; Pressure relief devices, valves, nonreclosing, liquid pressure relief valves, marking, certification of capacity of pressure relief devices, pressure setting, installation, minimun requirements for pressure relief valves, minimun requirements for rupture disk devices, capacity conversions safety valves, determination of certified relieving capacities